Gingermelon's embroidered animals : heirloom animal dolls to sew, embellish, and treasure - Down, Shelly (SewandSo, an imprint of F&W Media International, 2019)
"An exquisite collection of toy sewing patterns to make stuffed animals to treasure! These stunning animal dolls are easy to sew and then embellish with simple hand embroidery stitches to beautiful effect. The dolls and their cute outfits all use small amounts of fabric, so are great for using up scraps. With step-by step instructions and full guidance on the embroidery stitches and full-size pattern pieces to trace from the page, this super-accessible book will help you make future heirlooms that will stay in the family for generations." --